A Survey on Plagiarism among Vocational Students in ESP Setting - Ira Mutiaraningrum; Sri Lestari; Tiara Nove Ria; Nurfisi Arriyani (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
There has been a growing concern about plagiarism among students. This survey sets forth first-year vocational college students' knowledge of plagiarism. A 10-item survey was distributed to vocational students enrolled in the course of English for Specific Purposes. This study reveals that most students are unclear if they should give credit to the author, especially if they have previously paraphrased the line. They believe that unintentional plagiarism occurs mostly due to short deadlines for assignments, pressure to earn a decent score, and the notion that assignments are mere formalities that will not be examined by lecturers. According to the findings of this study, students lack adequate quoting and paraphrasing skills. Despite having insufficient knowledge of plagiarism, students were eager to learn how to avoid plagiarism. This study suggest the difficulty of students in reading paper in English. This study urges senior high school teachers to introduce plagiarism ethics to students. Lecturers and college staff are encouraged to train students to avoid plagiarism as early as possible, especially for vocational college students who have less time dealing with theories in the classroom.